Guidance for Supervisory Board Members of Banks - International Finance Corporation (International Finance Corporation, Washington, DC, 2017)
This manual, for present and prospective Supervisory Board (SB) members of non-complex banks, is intended to provide a guide to international best practice. It is designed to help SB in a practical way attend and maintain high standard of internal governance. This manual provides an overview. SB members are advised to familiarize themselves with the scope of the relevant legislation as they may be personally liable for breaches of certain provisions. This manual gives SB members fundamental understanding of their tasks. For more publications on IFC Sustainability please visit www.ifc.org/sustainabilitypublications.